Making Women Pay : The Hidden Costs of Fetal Rights - Roth, Rachel (Book collections on Project MUSE., 2000)
When a corporation, medical authority', or the state asserts or accepts rights claims on behalf of a fetus, the usual justification involves improving the chance of a healthy birth. This strategy, Roth persuasively argues, is not necessary to achieve the goal of a healthy birth, is oftencounterproductive to it, and always undermines women's equal standing.